Implementation Of Data Security Using Hill Cipher Algorithm - Insidini Fawwaz; N P Dharshinni (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
Cryptography is the science and art of keeping messages safe from being known by unauthorized persons. Most cryptography uses mathematical calculations both in calculating the secret key and in calculating the secret code that will be used. Thus, the information in the message will be kept safe and confidential. One of the classic cryptographic algorithms that can be used to ensure data security and security is the Hill Cipher method. Hill cipher is symmetric cryptography, also known as hill code, which is the application of modulo arithmetic to cryptography. This cryptographic technique uses a rectangular matrix as the key used for encryption and decryption. The system created can be used as data encoding in the form of characters in the form of letters by dividing block each encrypted character.